(untitled) (International Journal of Economics Management and Social Science, 2026)
Max Weber’s theory of social action and rationality remains a fundamental framework for understanding the dynamics of modern organizations and bureaucratic processes. This article analyzes the relevance of Weber’s concepts of social action, instrumental rationality, and rational bureaucracy in the context of contemporary organizations. Through a qualitative approach employing systematic literature review of Weber’s classical works and recent empirical studies (2018-2025), this research explores how rationalization processes shape the structure and practices of modern organizations. Findings indicate that Weber’s ideal-typical bureaucracy—characterized by formal hierarchy, functional specialization, impersonal rules, and technical competence—remains highly relevant yet faces significant challenges in the era of digitalization and organizational transformation. The rationalization paradox emerges when efforts to enhance efficiency create structural rigidity, worker alienation, and an iron cage of rationality that constrains creativity and innovation. This article identifies three critical dimensions: (1) the transformation of value-rational action (wertrational) into instrumental-rational action (zweckrational) in modern organizations; (2) the impact of rational bureaucracy on dehumanization and loss of work meaning; and (3) tensions between technical efficiency and humanistic values. The theoretical implications of this research enrich the understanding of organizational sociology by integrating classical Weberian perspectives with contemporary organizational realities, while practical implications suggest the need for rehumanization of bureaucracy through balancing instrumental and substantive rationality in 21st-century organizational design. Keywords: Max Weber, Social Action, Rationality, Bureaucracy, Rationalization, Modern Organizations, Iron Cage